REVITALISASI PEMBELAJARAN FIKIH MELALUI PELATIHAN PRAKTIS FIKIH JENAZAH DI LINGKUNGAN PESANTREN AR-RASYID - Firman Priyanto; Evie Puhan, Junita; Mayukha, Tuti; Ali Mustofa, Triono (Jurnal Al Basirah, 2025)
Knowledge and skills in managing the deceased are essential components of Islamic teachings and considered a collective obligation (fardhu kifayah). However, fiqh education on funeral rites in Islamic institutions remains largely theoretical and lacks practical application. This study aims to revitalize fiqh learning through practical training on Islamic funeral management at Ar-Rasyid Islamic Boarding School, Wonogiri. Using a Participatory Action Research (PAR) approach, the program involved students from junior to senior high school levels. The training consisted of three stages: theoretical material delivery, demonstration, and hands-on practice. The results showed a significant improvement in students' understanding and practical abilities regarding proper Islamic funeral procedures. Beyond technical skills, the training fostered spiritual and social awareness, contributing to the character development of the students. This initiative effectively strengthens the role of the pesantren as a contextual and practical center of Islamic education. Keywords: Revitalizing, Fiqh, Funeral, Practical Training, Islamic Boarding School